Geolocators reveal migratory connectivity between wintering and breeding areas of Golden‐winged Warblers. Issue 3 (September 2017) - Larkin, Jeffery L.; Raybuck, Douglas; Roth, Amber; Chavarría‐Duriaux, Liliana; Duriaux, Georges; Siles, Moisés; Smalling, Curtis
Abstract: The conservation of migratory songbirds is often impeded by a lack of understanding of how populations in breeding and wintering areas are geographically linked (migratory connectivity). In recent years, light‐level geolocators have improved our understanding of migratory connectivity. Such information is valuable for evaluating how conservation efforts align between the breeding and non‐breeding areas of at‐risk species, and help to more effectively prioritize the allocation of conservation funding. Golden‐winged Warblers ( Vermivora chrysoptera ) are imperiled migratory songbirds, but the extent to which conservation efforts in their breeding and non‐breeding areas coincide with patterns of migratory connectivity are not well known. We used light‐level geolocators to evaluate the extent to which conservation actions targeting Golden‐winged Warblers in Nicaragua and in their breeding range in North America align with patterns of migratory connectivity. We recovered six of 22 geolocators that had been deployed on male Golden‐winged Warblers at the El Jaguar Reserve during the winter of 2015–2016. All six males migrated to breeding areas in the western Great Lakes region that includes eastern Minnesota, northern Wisconsin, southwestern Ontario, and Michigan's Upper Peninsula. All six males also had similar migration routes, with spring stopovers in southern Mexico, Guatemala, and Belize, a trans‐Gulf flight, and a stopover in the region of Louisiana, Arkansas, eastern Oklahoma, and Texas. Our results, in combination with those of previous studies, demonstrate strong migratory connectivity between portions of the breeding and winter distributions of Golden‐winged Warblers currently targeted for conservation. However, additional studies are needed to improve our understanding of the stopover ecology of Golden‐winged Warblers, especially in areas where they remain for extended periods of time. Finally, patterns of migratory connectivity revealed in our study should be used in combination with existing demographic parameters for Golden‐winged Warblers in the western Great Lakes and Nicaragua to help inform full life cycle population models for this imperiled songbird.